Study on the relationship between homocysteine and general metabolic indexes in healthy population in Hebei Province, China - Feng, Hongru; Wang, Xiaoliang; Yu, Lili; Zheng, Qianqian; Wang, Zhaoqi (Frontiers in Endocrinology, 2025)
BackgroundThe aging problem is a significant issue and challenge currently faced by the whole world. Hyperhomocysteinemia (HHcy) is a common phenomenon among the older adult. Increasing evidence suggests a link between HHcy and multiple systemic issues in the older adult-related diseases. Therefore, the identification of high-risk factors for HHcy in a healthy screening population can effectively regulate the occurrence, progression of HHcy, thereby reducing the incidence of older adult-related diseases.MethodsA total of 10,511 individuals who underwent a comprehensive health examination at the Second Hospital of Hebei Medical University, China from 2021 to 2022 were included. Data on gender, age, carotid ultrasound(CCA), blood pressure(BP), body mass index(BMI), serum levels of homocysteine(Hcy), total cholesterol(TC), triglycerides(TG), low-density lipoprotein(LDL-C), high-density lipoprotein(HDL-C), alanine aminotransferase(ALT), aspartate aminotransferase(AST), red blood cells(RBC), creatinine(Cr), urea, uric acid(UA), fasting blood-glucose(FBG), and glycated hemoglobin(GHb) concentration were collected.ResultsHyperhomocysteinemia was associated with gender, age, BP, CCA, BMI, elevated levels of TC, TG, LDL-C, Cr, urea, UA, as well as decreased levels of HDL-C and RBC. Among these factors male, above 65 years old age, hypertension, carotid artery abnormalities, UA, and Cr were identified as independent risk factors, while HDL-C and RBC were identified as protective factors.ConclusionThe prevalence of HHcy was very high during routine physical examination especially the senior citizens in Hebei Province, China. Therefore, high-risk populations should be the focus of public health policies, and strengthening early intervention can reduce the occurrence of HHcy, thereby delaying the onset and progression of older adult-related diseases.